2010
DOI: 10.4103/0971-4065.65300
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of aminophylline prophylaxis of renal impairment after coronary angiography in patients with chronic renal insufficiency

Abstract: This study was done to investigate whether aminophylline reduces the incidence of contrast induced nephropathy (CIN) after coronary angioplasty. Sixty patients who had serum creatinine concentration of > 1.3 mg/dl randomly received 250 mg IV aminophylline or placebo 30 minutes before coronary angiography. Serum creatinine and blood urea nitrogen were determined immediately before (base line) and at 24 and 48 hours after administration of contrast medium. The primary end point was the incidence of CIN. The inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…A large number of drugs have been used to protect renal function after PCI, such as aminophylline (Shammas et al 2001;Rohani 2010), theophylline (Wang et al 2001), atrial natriuretic peptide (Chen 2009;Morikawa et al 2009), B-type natriuretic peptide (Zhang et al 2010), mannitol (Kelly et al 2008), prostaglandins (McCullough andTumlin 2009), N-acetylcysteine (Thiele et al 2010), sodium bicarbonate (Masuda 2008) and statins (Xinwei et al 2009); however, few of them (Kowalczyk et al 2007;Zoungas et al 2009) have shown exact protective effects.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of drugs have been used to protect renal function after PCI, such as aminophylline (Shammas et al 2001;Rohani 2010), theophylline (Wang et al 2001), atrial natriuretic peptide (Chen 2009;Morikawa et al 2009), B-type natriuretic peptide (Zhang et al 2010), mannitol (Kelly et al 2008), prostaglandins (McCullough andTumlin 2009), N-acetylcysteine (Thiele et al 2010), sodium bicarbonate (Masuda 2008) and statins (Xinwei et al 2009); however, few of them (Kowalczyk et al 2007;Zoungas et al 2009) have shown exact protective effects.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the concentration of adenosine in renal tissue with renal injury caused by ischemia or nephrotoxic agents supposes that adenosine is an important intrarenal factor in the pathogenesis of acute renal impairment [5]. It has also reported that inhibition of adenosine reuptake by dipyridamole induced the reduction of GFR and significantly increases the severity of renal impairment in response to CM and causes to a 70% decreasing in total reperfusion [5,28,29].…”
Section: Increasing In the Creatinin And Or Cystatin -C Level N (%) Amentioning
confidence: 99%
“…It has also reported that inhibition of adenosine reuptake by dipyridamole induced the reduction of GFR and significantly increases the severity of renal impairment in response to CM and causes to a 70% decreasing in total reperfusion [5,28,29]. In a study, Latham et al observed that dipyridamole infusion reduced renal blood flow and GFR measured by time-activity curves of left and right kidney by using Tehnetium-99-DTPA in healthy five patients [8].…”
Section: Increasing In the Creatinin And Or Cystatin -C Level N (%) Amentioning
confidence: 99%
See 2 more Smart Citations